Once again about poetry translation, or translation exercises - Bednarczyk, Anna (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The author of the article examines the problems of poetic translation by analyzing two existing translations of Nikolai Gumilyov’s poem Mechta (Dreams) in the context of adequacy of the semantic and stylistic layers of the text, and above all, from the point of view of the purpose of translation. The article discusses a third translation, which has even acquired a musical design by Konstantin Regamey. The analysis leads to the conclusion that, considering the existing translation, it is necessary to pay attention not only to microshifts but to study it as a whole. In turn, when making “countertranslation,” one should take into account both the objective and subjective dominants of the translation, including the purpose of its implementation.